Implementing State Defense Strategy to Achieve Sustainable Tourism in Sleman Regency - Agussalim, Agussalim; Heriningsih, Sucahyo; Heriyanto , Heriyanto (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This study aims to analyze the role of the State Defense (Bela Negara) strategy in achieving sustainable tourism in Sleman Regency. Sleman Regency possesses significant tourism potential, which necessitates sustainable development to ensure the preservation of its natural and cultural resources, improvement of service quality, and empowerment of local communities. This research employs descriptive qualitative methods, including interviews, observations, and literature studies, to explore these issues. The findings reveal that the Bela Negara strategy significantly contributes to sustainable tourism through enhanced environmental awareness, increased community participation, and multi-stakeholder collaboration in protecting natural resources, culture, and the environment. Tourism actors also continuously work on improving service quality and strengthening local communities through training, job creation, and cultural preservation. These efforts lead to the betterment of service quality, environmental conservation, and cultural preservation, ensuring the overall sustainability of tourism in the region. This study provides a deeper understanding of the importance of the Bela Negara strategy and highlights the need for increased cooperation among stakeholders for sustainable tourism development. The results underscore the critical role of a well-planned Bela Negara strategy that integrates social, economic, and environmental aspects to achieve sustainable tourism development in Sleman Regency.